A dual-genome microarray for the pea aphid, Acyrthosiphon pisum, and its obligate bacterial symbiont, Buchnera aphidicola - Hunter Wayne B; Davis Gregory K; Dunbar Helen E; Wilson Alex CC; Stern David L; Moran Nancy A (BMC Genomics, 2006)
Abstract Background The best studied insect-symbiont system is that of aphids and their primary bacterial endosymbiont Buchnera aphidicola. Buchnera inhabits specialized host cells called bacteriocytes, provides nutrients to the aphid and has co-speciated with its aphid hosts for the past 150 million years. We have used a single microarray to examine gene expression in the pea aphid, Acyrthosiphon pisum, and its resident Buchnera. Very little is known of gene expression in aphids, few studies have examined gene expression in Buchnera, and no study has examined simultaneously the expression profiles of a host and its symbiont. Expression profiling of aphids, in studies such as this, will be critical for assigning newly discovered A. pisum genes to functional roles. In particular, because aphids possess many genes that are absent from Drosophila and other holometabolous insect taxa, aphid genome annotation efforts cannot rely entirely on homology to the best-studied insect systems. Development of this dual-genome array represents a first attempt to characterize gene expression in this emerging model system. Results We chose to examine heat shock response because it has been well characterized both in Buchnera and in other insect species. Our results from the Buchnera of A. pisum show responses for the same gene set as an earlier study of heat shock response in Buchnera for the host aphid Schizaphis graminum. Additionally, analyses of aphid transcripts showed the expected response for homologs of known heat shock genes as well as responses for several genes with unknown functional roles. Conclusion We examined gene expression under heat shock of an insect and its bacterial symbiont in a single assay using a dual-genome microarray. Further, our results indicate that microarrays are a useful tool for inferring functional roles of genes in A. pisum and other insects and suggest that the pea aphid genome may contain many gene paralogs that are differentially regulated.